Hummingbird–plant interactions in high-mountain gardens: a case study at Paraíso Quetzal Lodge and finca Doña Blanca (Los Santos, Costa Rica, 2024) (Biocenosis, 2025)
Hummingbird–plant interactions were assessed in two high‐mountain gardens in Los Santos, Costa Rica (Paraíso Quetzal Lodge and finca Doña Blanca; 2,650–2,700 m) in April–June 2024 using standardized plot observations (10-min windows with morning/ afternoon repetitions). Seven hummingbird species were recorded, and garden floristic composition was characterized. Visitation concentrated on a reduced set of nectar-rich, morphologically compatible plants—primarily Streptosolen jamesonii, Stachytarpheta mutabilis, Fuchsia spp., and Myrcianthes storki, while several ornamentals showed marginal or no interaction. Proximity of perches (shrubs/trees) and vertical stratification were associated with longer stays and returns of the birds, which explains differences between a consolidated and an emerging garden. These patterns allow the following design guidelines: 2–3 core species with sustained flowering, one “node plant,” nearby perches, short distances between nectar “islands” and perches, dense blocks, and staggered phenological management (an agricultural strategy that involves scheduling and spreading the stages of flowering, fruiting, or harvesting of a plant over time). The findings provide an operational basis to strengthen hummingbirds conservation and local birdwatching in high-mountain settings.
Keywords: hummingbird conservation; perches; pollinator gardens; ecological design; birdwatching tourism